Implementation of Two-Factor Authentication (2FA) Using a REST API-Based WhatsApp Gateway to Prevent Fake Bidders on an Online Auction Platform - Rizky Parlika; Hamdi Indra; Tegar Satria Kirana (Yayasan Ibrahim Learning Centre Agam, 2026)
Account security and identity validity are crucial aspects of online auction platforms to prevent price manipulation by fake bidders. Conventional authentication methods are often vulnerable to cyber-attacks or compromise user convenience for the sake of security. This study aims to implement a Two-Factor Authentication (2FA) system on the Mokasindo auction platform using WhatsApp Gateway integrated via REST API technology. The development method includes Webhook mechanisms for real-time user phone number validation and AJAX Short Polling techniques to deliver auto-login features without page refreshing. Black Box testing results indicate that the system successfully verifies user identity accurately and mitigates the risk of fictitious account registration. This implementation offers an optimal balance between system security and User Experience (UX), with an average recorded verification process latency of only 3.5 seconds. This solution proves effective in creating a more secure, responsive, and trustworthy auction ecosystem for users.